System and Mechanism Islamic Education Leadership in Indonesia - Muslihatuzzahro, Finy (CV. Creative Tugu Pena, 2022)
In Islamic educational institutions or organizations, the function of leaders has a very strategic position in an effort to realize educational goals and increase human resources (HR) to be able to be competitive in various fields. Therefore, leaders do not only function structurally. But more than that, the leader is a leader who must be able to realize the goals and programs of the institutions that have been planned. Thus, given how important leadership systems and mechanisms are in Islamic education. This research method is classified as qualitative research, with a literature study approach and is descriptive-analytical, data analysis this time through the data reduction stage, namely selection, concentration of discussion, abstraction of the entire grand data to several selected data needed. The results of this study show that leadership in an Islamic educational organization or institution is something very important. Because the existence of leadership or leadership can determine the success or failure of an institution in the vision, mission and goals of the institution. The urgency of the leadership is rooted in the process of soldering in Islamic educational institutions, and is also inseparable from the role of provincial and central regional offices and the rank of consideration bodies in the leadership of the education. Keywords: Islamic System, Islamic Education Leadership, Mechanism Islamic Education